Avaliação das atividades de crianças com paralisia cerebral na escola regular : participação, níveis de auxílio e desempenho. - Silva, Daniela Baleroni Rodrigues (2007)
Facing the great debate on the inclusion of students with special needs, this study investigated the involvement, level of support and activities performances of children with cerebral palsy on the school context through the School Function Assessment ( SFA ). It also demonstrates the valuation s contributions through the presentation of a case on the identification of the capacities and limitation of those students and also to determine possible intervention points along with the teacher. On this study, 10 teachers and their respective students with cerebral palsy of public and private schools in São Paulo and neighbor cities were involved. Was applied the SFA the consists of a test in questionary s format systematized answered by the teachers. The results indicated children s involvement were more restricted on the restrooms, transportation and transitions, once that those environments demanded practice of physical tasks such as go to the restrooms, managing clothes flushing the toilet, embark and disembark of schools transportation and move inside the school. It also notable high levels of assistance on the execution of those tasks and minimal or no adaptation in environment as restrooms or adapted vehicles, such as a flat surface of easy access at schools. Also, the use of mobility resources such as crutches and walkers consisted as important facilitators of participation, opposite of the students who moved helped by other people. Regarding the cognitive/behavior aspects required at school like memory, attention, communication and integration with classmates and adults, it s notable that happened minimal limitation that consists in favorable points for inclusion in regular schools. It is also accentuated the importance of special education professionals such as occupational therapists, physical therapists, on the school environment in order to accomplish the as with the teachers to potentiate the participation those students. Also, it s necessary governmental actions for introduce environment s adaptations at schools.